Plant-derived compounds stimulate the decomposition of organic matter in arctic permafrost soils - Birgit Wild (University of Vienna); Norman Gentsch (Institute of Soil Science, Leibniz Universität Hannover); Petr Čapek (Department of Ecosystem Biology, University of South Bohemia); Kateřina Diáková (Department of Ecosystem Biology, University of South Bohemia); Ricardo J. Eloy Alves (Department of Ecogenomics and Systems Biology, Faculty of Life Sciences, University of Vienna); Jiři Bárta (Department of Ecosystem Biology, University of South Bohemia); Antje Gittel (Department of Biology, Centre for Geobiology, University of Bergen); Gustaf Hugelius (Department of Physical Geography, Stockholm University); Anna Knoltsch (University of Vienna); Peter Kuhry (Department of Physical Geography, Stockholm University); Nikolay Lashchinskiy (Central Siberian Botanical Garden, Siberian Branch of Russian Academy of Sciences); Robert Mikutta (Institute of Soil Science, Leibniz Universität Hannover); et al. (Scientific Reports, 2016)
The abstract is available here: https://uscholar.univie.ac.at/o:561364 The abstract is available here: https://uscholar.univie.ac.at/o:561364